Empirical industrial organization economics to analyze developing country food value chains - Macchiavello, Rocco; Reardon, Thomas; Richards, Timothy J. (Annual Reviews, 2022)
Food value chains (FVCs) in developing countries are transforming rapidly, with some regions in the modern stage (led by supermarkets and large processors) and other regions in a transitional stage (led by midstream small and medium enterprises). With transformation, however, come market-performance issues related to monopoly and monopsony power, vertical bargaining, contracting, and other issues addressed by empirical industrial organization (EIO) researchers. Although the concepts and methods of EIO are evolving rapidly, the two bodies of literature on EIO and FVC transformation as part of the food markets and food industries branches of development economics have not sufficiently cross-pollinated. Applying tools of modern EIO to FVCs in developing countries is now relevant because of the transformation that has occurred and possibly due to the increasing availability of data from surveys of farms, processors, and wholesalers, and for some retailers, from scanner data. We review the transformation trends, the EIO themes and tools relevant to them, and the emerging data sources.